Routledge Companion to Narrative Theory - Dawson, Paul; Mäkelä, Maria (Taylor & Francis, 2023)
The Routledge Companion to Narrative Theory brings together top scholars in the field to explore the significance of narrative to pressing social, cultural, and theoretical issues. How does narrative both inform and limit the way we think today? From conspiracy theories and social media movements to racial politics and climate change future scenarios, the reach is broad. This volume is distinctive for addressing the complicated relations between the interdisciplinary narrative turn in the academy and the contemporary boom of instrumental storytelling in the public sphere. The scholars collected here explore new theories of causality, experientiality, and fictionality; challenge normative modes of storytelling; and offer polemical accounts of narrative fiction, nonfiction, and video games. Drawing upon the latest research in areas from cognitive sciences to complexity theory, the volume provides an accessible entry point for those new to the myriad applications of narrative theory and a point of departure for new scholarship.